Rapid-Sequence Intubation in the Left-Lateral Tilt Position in a Pregnant Woman with Premature Placental Abruption Utilizing a Videolaryngoscope - Nakao, Kenta; Komasawa, Nobuyasu; Kusaka, Yusuke; Minami, Toshiaki (American Journal of Perinatology Reports, 2015)
Case A 24-year-old pregnant woman was admitted to our hospital with decreased fetal heart rate. Obstetric examination revealed premature placental abruption; emergent caesarean section was planned under general anesthesia. On entering the operating room, the patient showed severe vital sign deterioration (blood pressure, 75/45 mm Hg; heart rate, 142 beats per minute). As left uterine displacement may worsen the premature placental abruption, the patient was placed in the left-lateral tilt position by rotating the operating table to release compression on the inferior vena cava by theuterus. To avoid circulatory collapse, rapid-sequence intubation was performed in this position. Tracheal intubation was performed with the Pentax-AWS Airwayscope (AWS videolaryngoscope, AWS; HOYA, Japan) to obtain a good laryngeal view and minimize stress from laryngoscopy. After sufficient oxygenation, 120 mg of thiopental was administered. A second anesthesiologist performed cricoid pressure and 50 mg of rocuronium was administered after confirming loss of consciousness. This was followed by insertion of the AWS with a thin intlock into the mouth. Tracheal intubation was performed uneventfully.Discussion Rapid-sequence intubation in the left-lateral tilted position with the AWS videolaryngoscope may be beneficial for pregnant women with vital sign deterioration.
Keywords: rapid-sequence intubation; videolaryngoscope; left-lateral tilt position; premature placental abruption